Inhibitory effect of sulphated polysaccharide porphyran (isolated from Porphyra yezoensis) on RANKL‐induced differentiation of RAW264.7 cells into osteoclasts. (11th December 2017) - Ueno, Mikinori; Cho, Kichul; Isaka, Shogo; Nishiguchi, Tomoki; Yamaguchi, Kenichi; Kim, Daekyung; Oda, Tatsuya
Abstract : Safe and efficient therapeutic agents for bone diseases are required in natural sources. We previously found that edible seaweed‐derived polysaccharide porphyran exhibited anti‐inflammatory effects through the down regulation of nuclear factor‐κB. The aim of this study was to investigate the availability of porphyran as a therapeutic agent for bone diseases. The effects of porphyran on receptor activator of nuclear factor κB ligand (RANKL)‐induced osteoclastogenesis in RAW264.7 cells were examined. Porphyran suppressed RANKL‐induced osteoclast formation in a concentration‐dependent manner (6.25–50 μg/ml) without any cytotoxic effects. Furthermore, real‐time polymerase chain reaction analyses indicated that porphyran at 50 μg/ml significantly attenuated the RANKL‐induced increase in the mRNA levels of osteoclastogenesis‐related marker genes such as nuclear factor of activated T cells, tartrate‐resistant acid phosphatase, cathepsin K, and matrix metalloproteinase‐9 in RAW264.7 cells. To our knowledge, this is the first report showing that edible‐seaweed‐derived polysaccharide porphyran can suppress RANKL‐induced osteoclastogenesis. Our results suggest that porphyran can be used as a safe therapeutic agent to improve osteoclast‐related pathological conditions.